Improving Students’ Ability In Writing Recount Text Through Contextual Teaching And Learning (Ctl) Approach At The Second Grade Student Of SMA DHI MAPILLI - Aymu Alamia Haidir (Journal of Research Education and English Teaching, 2025)
This research aimed to find out improvement the students’ ability in wiriting recount text through contextual teaching and learning (CTL) approach at the second grade student of XI Social Science 1 of SMA DHI MAPILLI in academic year of 2018/2019. The mean scores in cycle II is greater than the mean score of test in cycle I (75.83>64.13). the implementation of Contextual Rteachinghat there were six meetings for two cycles. This classroom action research was done at the second grade student of SMA DHI MAPILLI. The subject of this research was XI Socisl Science 1 class in academic year of 2018/2019 by using contextual teaching and learning (CTL) approach. It consisted of 30 students. The implementiation of this research was giving the improvement for the result of the students’ ability in writing recount text through contextual teaching and learning (CTL) approach and the teacher activities in teaching and learning process. The mean scores of writing recount text in the first cycle was 64.13, and after revision in the second cycle, the mean scores became 75.83. the improvement of students’ ability to write recount text through Contextual Teaching and learning (CTL) approach is presenting recount text material at XI Social Science 1 class of SMA DHI MAPILLI. Improves the students’ ability significantly. The mean scores in cycle II is greater than the mean score of test in cycle I (75.83>64.13). the implementation of Contextual Rteaching and Learning (CTL) approach can make the students more active and enthusiast in learning process